2014
DOI: 10.2478/ppb-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

EAS Temperament Traits, Gender, Age and Religious Fundamentalism in a Polish Sample

Abstract: This is a study of the relationship between EAS temperament traits, age and gender, and religious fundamentalism in an adult Polish sample. Participants were sampled from among people who tended towards secularisation. A total of 902 participants, including 551 women and 351 men, aged 18 to 58 (M=27.73; SD=7.40) were studied. Participants were students in a variety of university faculties and adults with higher education representing a variety of professions. They all lived in the Warsaw area. Temperament was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…To measure temperamental traits, we used The Temperament EAS Survey [20] adapted by Oniszczenko (1997) [21], in two versions: EAS-TS for Adults (EAS-D) and EAS-TS for Children: Parental Ratings (EAS-C). Each of these versions consists of 20 items, which are assessed by the respondents on a 5-point scale (from 1-definitely not to 5-definitely yes).…”
Section: Methodsmentioning
confidence: 99%
“…To measure temperamental traits, we used The Temperament EAS Survey [20] adapted by Oniszczenko (1997) [21], in two versions: EAS-TS for Adults (EAS-D) and EAS-TS for Children: Parental Ratings (EAS-C). Each of these versions consists of 20 items, which are assessed by the respondents on a 5-point scale (from 1-definitely not to 5-definitely yes).…”
Section: Methodsmentioning
confidence: 99%
“…Los datos acerca del género y edad son similares a otras investigaciones realizadas en muestras análogas 18,19 , aun cuando otros autores reportan un rango de edad superior 20,21 y Fondevila y Del Olmo 22 difieren en que las mujeres otorgan a la orientación religiosa de la formación una cifra ligeramente inferior (1,61%) con respecto a los hombres (1,68%). Igualmente, los roles sociales tradicionales de género, determinan las diferencias entre hombres quienes eligen carreras técnicas, y mujeres quienes prefieren carreras sociales y de humanidades en la elección de la profesión (el deseo de servicio a la sociedad y la vivencia de experiencias médicas) 23 .…”
Section: Discussionunclassified
“…A meta-analysis of research on children exploring differences in 35 temperamental traits showed that boys score higher for activity, but differences in negative affectivity attributable to sex are negligible (Else-Quest et al, 2006). It may be that adult women systematically obtain higher scores on measures of EAS fearfulness than men because they are gender-socialized in different ways (Buss & Plomin, 1984;Oniszczenko, 1997;Oniszczenko et al, 2014).…”
Section: Sexmentioning
confidence: 99%